Elaboração de pão com casca de abacate hass: valor nutricional e aceitabilidade - Fumes, Joana Giffoni Figueiredo [UNESP] (2015)
The avocado is a nutritious fruit that has high antioxidant potential. The components responsible for this feature are present not only in the flesh, but in the shell and core of fruit. Recent research shows the high potential antioxidant from the bark. Therefore, the aim of this project was to develop mass breads with added avocado peel 'Hass' in its formulation. The incorporation of the shell in a product such as homemade bread, creates an alternative to the consumption of nutrients, minerals and antioxidants that bring many benefits to the human body. The raw materials used were avocados collected and selected as the default of mechanical injuries aiming the homogenizing of the lot. The cleaning fruits was made with sodium hypochlorite 5% solution for 10 minutes and leave to dry at room temperature. After they were completely dry, the fruits were cut and separated peel, pulp and seed. As the peels stored in the freezer packaging polypropylene. Three experiments were designed. Experiment I: formulation of breads with (50g, 100g and 150g peel); Experiment II: fermentation time of breads (30min, 60min and 90min); Experiment III: cooking time of breads (20min, 25min and 30min). Three sensory analyzes were performed in breads ...